Magickeepers: The Pyramid of Souls (Magickeepers, ,)
In this next installment of the thrilling MagicKeepers series, Nick must save his family's very souls from the evil sorcerer Rasputin. Nick Rostov finally has the life he's always dreamed—and he'll do anything to protect it. Nick has only now discovered he is part of an extended Russian family of magicians: the Magickeepers. He lives with his eccentric new relatives at the Winter Palace Hotel and Casino in Las Vegas, where they perform daring feats of magic to a packed house. Real magic. But Nick and his family face a new danger in the form of a stolen relic, the Pyramid of Souls. The tiny pyramid has traded hands many times throughout history. Its power can steal a magician's very soul. Nick knows who took it: Rasputin, leader of the Shadowkeepers. Using his unique ability as a Gazer—one who can see into the past—Nick enlists his cousin Isabella to help him find it. Soon, the two are hot on the evil sorcerer's trail...until Isabella's soul is trapped by the very relic they're trying to find. Nick will do anything to rescue Isabella and recover the Pyramid of Souls. But will it be enough to save his family?

The Pyramid of Souls (Magickeepers, 2,, 2010)
Thirteen-year-old Nick Rostov and his large, extended family of Russian Magickeepers continue to battle the evil Shadowkeepers, who now seek a miniature pyramid of souls that once belonged to Edgar Allan Poe.